1055The applicability of the Healthy Eating Index to measure Iranian diet quality. (2nd September 2021) - Ebrahimi, Sara; Leech, Rebecca; McNaughton, Sarah; Livingstone, Katherine
Abstract: Background: Iranian diet quality has been evaluated using indices that are not based on Iranian dietary guidelines. This study examined the applicability of the Healthy Eating Index (HEI) by examining associations with sociodemographics, nutrient intakes and nutrient adequacy. Methods: Household sociodemographics and dietary intakes (three 24-h dietary recalls) were collected in the cross-sectional National Comprehensive Study on Household Food Consumption Patterns and Nutritional Status 2001-2003. Household diet quality was calculated using the HEI. Regression analyses examined associations between diet quality and sociodemographics, nutrient intakes and nutrient adequacy. Results: A total of 6584 households were included in this study. Age (β-coeff 2.11; 95% CI: 1.64, 2.44), education (β-coeff 4.58; 4.05, 5.11) and living in urban areas (β-coeff 2.87; 2.56, 3.19) (as reported by the household head) were positively associated with diet quality. Higher diet quality was associated with higher intake of protein (% energy) (β-coeff 0.08; 0.07, 0.08), calcium (mg/day) (β-coeff 12.10; 11.23, 12.98), iron (mg/day) (β-coeff 0.04; 0.02, 0.05), vitamin C (mg/day) (β-coeff 3.61; 3.45, 3.77) and fibre (g/day) (β-coeff 0.12; 0.11, 0.14), lower intake of sodium (mg/day) (β-coeff -83.45; -93.02, -73.88) and adequate intake of calcium (mg/day) (OR 1.10; 95% CI: 1.09, 1.12) and vitamin C (mg/day) (1.19; 1.18, 1.20). Conclusions: Higher HEI was associated with a range of sociodemographics and better nutrient intakes and nutrient adequacy. Key messages: HEI was applicable for assessing the diet quality of Iranian households.